SOME ASPECTS IN EARLY LIFE STAGES IN LARVA GREEN CATFISH, Mystus nemurus (Cuv, & Val) - Thumronk Amornsakun; Anuar Bin Hassan (Indonesian Fisheries Research Journal, 1997)
Larval green catfish were produced by induced spawning using extracted hormone (Buserelin and Domperidone) injection. Twenty newly-hatched larvae were sampled from the hatching tank at 2 hours intervals for observation of the yolk absorption process.